Reliability and validity of the total cerebral small vessel disease score: a systematic review and meta-analysis - Silva, Guilherme Diogo; Telles, João Paulo Mota; Rimkus, Carolina de Medeiros; Vieira, Germana Titoneli; Yuki, Emily Figueiredo Vieira Neves; Azevedo, Raymundo Soares de; Tinone, Gisela; Lucato, Leandro Tavares; Pereira, Rosa Maria; Conforto, Adriana Bastos (Frontiers in Neurology, 2025)
IntroductionCerebral small vessel disease (CSVD) is a research priority to reduce the burden of stroke and dementia. The total cerebral small vessel disease (tSVD) score provides a global view of CSVD burden combining lacunes of presumed vascular origin, cerebral microbleeds, enlarged perivascular spaces, and white matter hyperintensities of presumed vascular origin. While its use in research is expanding, a systematic review of the tSVD score’s reliability and validity had not yet been undertaken. We reviewed the inter-rater and intra-rater reliability for the tSVD score and its features. We also examined the associations between the tSVD score and age, hypertension, stroke and cognitive impairment.MethodsWe performed a systematic review of studies on Pubmed/MEDLINE, Embase, and Scopus databases from inception until June 21st, 2024. We included manuscripts that reported at least one of the following metrics for the tSVD or for its components: inter-rater reliability, intra-rater reliability, or associations with age, hypertension, stroke, and/or cognitive impairment. We provided summary Cohen’s kappa coefficients for inter and intra-rater reliability for each feature of the tSVD score. Subgroup analysis and meta-regression models were used to evaluate the impact of raters, MRI fields, age, and median tSVD score values in inter-rater reliability. We summarized studies reporting associations between the tSVD score, stroke and cognitive impairment.ResultsThe summary Cohen’s kappa values for inter-rater reliability ranged from 0.79 to 0.82 for each CSVD feature (13 studies, 8,177 participants). We found a high heterogeneity between studies (I2 = 94%), which may be explained by differences in rater, age, and median tSVD score. The summary Cohen’s kappa values for intra-rater reliability ranged from 0.78 to 0.84 (four studies, 250 cases were randomized from 3,654 participants). Heterogeneity was low. Seven studies (6,022 participants) reported associations between tSVD scores and either age or hypertension. Fifteen studies (6,941 participants) reported associations between tSVD scores and either stroke or cognitive impairment.ConclusionThe intra-rater reliability, inter-rater reliability, and construct validity of each feature of the tSVD support the use of this scale in CSVD research. However, inter-rater reliability might be influenced by rater characteristics, the median tSVD score, and participant age.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42022372599.